Red Hat Certified Engineer (RHCE) - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2016)
Red Hat Certified Engineer (RHCE) Complete Video Course is a unique video product that provides a solid understanding of all the topics that are required to pass the Red Hat Certified Engineer (RHCE) exam. This title explores how to accomplish advanced system administration tasks, such as writing shell scripts, troubleshooting a server boot procedure, working with SELinux and firewalls and configuring different network services. Red Hat Certified Engineer (RHCE) Complete Video Course contains 17 individual video lessons divided into four modules, for a total of more than 8 hours of training. The videos consist of live trainer instruction, white board training, CLI presentations, live demos, video screen casts and practice exam walk-throughs. The author covers all of the objectives in the exam so you can use this course as a complete study tool for taking the Red Hat Certified Engineer (RHCE) exam. Each lesson ends with a practice exercise, so you can practice within a CLI environment and put your knowledge to the test. Complete explanations for each exercise are also offered so you can check your work. Red Hat Certified Engineer (RHCE) Exam Prep Workshop contains more than 4 hours of deep-dive training on common RHCE exam traps, pitfalls, and difficulties. Sander van Vugt, an experienced Red Hat instructor, trainer, and author will detail the most common mistakes people make when taking the RHCE exam, so you can avoid them in the testing facility. You will then walk through a live practice exam with the author in real-time, so you can experience first-hand what it’s like to take the test.